2017
DOI: 10.1038/ni.3690
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP12 attenuates colon inflammation by maintaining colonic microbial diversity and promoting protective commensal bacterial growth

Abstract: Inflammatory bowel diseases involve the dynamic interplay of host genetics, microbiome and inflammatory response. Here, we report that NLRP12, a negative regulator of innate immunity, is reduced in human ulcerative colitis by comparing monozygotic twins and other patient cohorts. In parallel, Nlrp12-deficiency in mice caused increased colonic basal inflammation, leading to a less-diverse microbiome, loss of protective gut commensal strains (Lachnospiraceae) and increased colitogenic strains (Erysipelotrichacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(243 citation statements)
references
References 51 publications
9
232
1
1
Order By: Relevance
“…Recently, Chen et al reported the nod-like receptor (NLR) p12 is crucial in attenuation of colon inflammation by promoting protective bacterial growth. The authors demonstrated that Nlrp12 deficient mice are susceptible to dysbiosis and colitis and exhibit similar changes to those observed in EAE induction, with a loss of Lachnospiraceae family members and increases in the abundance of the Erysipelotrichaceae spp (Chen et al, 2017). Strikingly, Nlrp12 deficiency was also shown to exacerbate EAE (Gharagozloo et al, 2015, Lukens et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Chen et al reported the nod-like receptor (NLR) p12 is crucial in attenuation of colon inflammation by promoting protective bacterial growth. The authors demonstrated that Nlrp12 deficient mice are susceptible to dysbiosis and colitis and exhibit similar changes to those observed in EAE induction, with a loss of Lachnospiraceae family members and increases in the abundance of the Erysipelotrichaceae spp (Chen et al, 2017). Strikingly, Nlrp12 deficiency was also shown to exacerbate EAE (Gharagozloo et al, 2015, Lukens et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…A. muciniphila induces colitis in specific-pathogen-free (SPF) Il-10 -/- mice, likely owing to its ability to degrade mucus and activate TLR4/MYD88 signaling (22**). Similarly, Chen et al demonstrated that NLRP12, whose expression is downregulated in UC patients, prevents microbiota-driven colitis (23*). Nlrp12 –/– mice have a less diverse microbiota characterized by decreased abundance of Lachnospiraceae and increased Erysipelotrichaceae, and displayed higher susceptibility to DSS colitis which can be suppressed by oral supplementation of Lachnospiraceae (23*).…”
Section: Innate Sensors and Immune Signalingmentioning
confidence: 97%
“…Body weight was monitored daily, and colon length and DAI were evaluated at the end of the experiment in accordance with adapted methods described previously. In brief, the DAI was the sum of scores of parameters as follows: weight loss, 0 weight loss = 0; 1–5% weight loss = 1; 5–10% weight loss = 2; 10–20% weight loss = 3; >20% weight loss = 4; rectal bleeding, negative = 0; positive Hemoccult test = 2; gross bleeding = 4; and faeces consistency, normal = 0; semiformed faeces = 2; liquid and adheres to the anus = 4 . And the caecum, colon and rectum close to anus were collected together, and the total length was measured …”
Section: Methodsmentioning
confidence: 99%